2010
DOI: 10.1002/bit.22934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antimicrobial tylosin on the microbial community structure of an anaerobic sequencing batch reactor

Abstract: Morgenroth, Eberhard; and Raskin, Lutgarde, "Effects of the antimicrobial tylosin on the microbial community structure of an anaerobic sequencing batch reactor" (2010). Civil Engineering Faculty Publications. 37. http://digitalcommons.unl.edu/civilengfacpub/37 AbstractThe effects of the antimicrobial tylosin on a methanogenic microbial community were studied in a glucosefed laboratory-scale anaerobic sequencing batch reactor (ASBR) exposed to stepwise increases of tylosin (0, 1.67, and 167 mg/L). The microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Our result is in agreement with that of Shimada et al [11], who reported that tylosin significantly decreased the relative abundance of Methanosaeta. However, Chelliapan et al [18] found that methanogens were well adapted to tylosin at levels of 100 and 800 mg=L in an up-flow anaerobic stage reactor (UASR).…”
Section: Methanogenic Archaea Diversity Of Slurrysupporting
confidence: 94%
See 1 more Smart Citation
“…Our result is in agreement with that of Shimada et al [11], who reported that tylosin significantly decreased the relative abundance of Methanosaeta. However, Chelliapan et al [18] found that methanogens were well adapted to tylosin at levels of 100 and 800 mg=L in an up-flow anaerobic stage reactor (UASR).…”
Section: Methanogenic Archaea Diversity Of Slurrysupporting
confidence: 94%
“…Shimada et al [10] reported that addition of TYL to anaerobic sequential batch reactor reduced the utilization of acetate, propionate, and butyrate and in addition, inhibiting saturated fatty acid, beta-oxidizing syntrophic and gram-positive homoacetogenic bacteria. More recently, Shimada et al [11] studied the effects of TYL on methanogenic V C 2013 American Institute of Chemical Engineers community in a glucose-fed laboratory-scale anaerobic sequential batch reactor reported that at high dose of 167 mg TYL=L, syntrophobacter species were not detected but the relative abundance of methanosaeta decreased considerably.…”
Section: Introductionmentioning
confidence: 99%
“…In batch tests, the specific biogas production was also completely inhibited in the presence of tylosin. According to these authors [10], this failure was the consequence of the direct inhibition of propionate-oxidizing syntrophic bacteria, closely related to Syntrophobacter and the indirect inhibition of Methanosaeta by high propionate concentration and low pH. This inhibition was also noticed by Stasinakis [11].…”
Section: Introductionmentioning
confidence: 86%
“…The microbial community can be very diverse both at the phylogenetic and functional levels 5 . While it is essential to maintain a proper microbial composition to assure efficient wastewater treatment 6,7 , the bioengineer has only a limited number of operational handles on the system. The operational variables include aeration, mixing and flow rate, which if not optimally chosen can lead to bioreactor failure 8 .…”
Section: Mathematical Models In Environmental Biotechnologymentioning
confidence: 99%